Digital HR Practices, Employee Digital Competence, and Transformational Leadership: A Work Engagement–Driven Model of MSME Performance - Santi Suciningtyas; Indri Putri Utami; Achmad Sholihin; Rita Andini; Amiruddin Qadaar; Julia Day Howell (Universitas Tidar, 2026)
The purpose of this study is to examine Digital HR (Human Resource) Practices, Employee Digital Competence, Transformational Leadership, and the impact of Work Engagement on MSME Performance within the thrifting industry of Indonesia. This study applies JD-R Theory and uses a quantitative explanatory method informed by employee surveys from 200 thrift MSMEs in Indonesia. We collected and analyzed data using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings suggest that Employee Digital Competence and Transformational Leadership positively affect Work Engagement, while Digital HR (Human Resource) Practices have a somewhat lower positive effect on Work Engagement. Work Engagement is positively and significantly correlated to MSME Performance and acts as a key mediator, especially in the interaction of Transformational Leadership with performance.On the other hand, Work Engagement’s mediating impact on Digital HR (Human Resource) Practices and MSME Performance is rather restricted. This indicates that the more ‘human’ resources are likely the more influential factor compared to ‘digital’ resources in improving MSME Performance. This study emphasizes the importance of Digital HR and MSME by stressing the importance of employees and leaders in engagement-based performance models.